Behavioural ecology, genetics and success of African wild dogs Lycaon pictus (Temminck, 1820) in KwaZulu-Natal, South Africa - Somers, Michael J. (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2011.